Economic analysis of crop protection strategies: comparing the value of increased fungicide inputs and crop genetic improvement in managing Ascochyta blight in Australian chickpeas - Olita, Toto; Cao, Zhanglong; Gibberd, Mark (John Wiley & Sons Inc., 2024)
BACKGROUND: Genetic improvement of crop varieties requires signiﬁcant investment. Therefore, varieties must be developed to suit a broad range of breeding targets, such as yield and suitability to rainfall zones, farm management practices and quality traits. In the case of breeding for disease resistance, breeders need to consider the value of genetic improvement relative toother disease management strategies and the dynamics of pathogen genetic and phenotypic diversity. This study uses a beneﬁt–cost analysis framework to assess the economic value of fungicide management and crop genetic improvement in dis-ease resistance for Australian chickpea varieties.